A cross-sectional survey exploring the attitude, knowledge, and use of anesthesia teams toward evidence-based practice in Riyadh Saudi Arabia - Al Anazi, Salem Khalaf; Al Zahrani, Waleed Abdullah; Alsanad, Mohammed Abdulaziz; Alzahrani, Matar Saeed; Al Ghamdi, Ibrahim Saeed; Alotaibi, Abdulmueen Awadh; Al maliki, Mohammed Ali; Asiri, Hamzah Mohammed; Alshehri, Ghirman Mohammed; Alanazi, Abdullah Salem; Al Anazi, Abdulelah Khalaf (Frontiers in Public Health, 2022)
Background Evidence-based practice (EBP) plays a crucial role in improving the quality of healthcare services by ensuring the delivery of the highest and safest level of patient care since EBP helps in justifying treatment choices to patients. Studies that examine the levels of EBP knowledge, attitudes toward EBP, and use of the use of EBP within anesthetic teams' practice are lacking, hence it is necessary to explore this. Aim To evaluate anesthesia teams' levels of knowledge, attitude toward and use of the evidence-based practice in a local hospital in Saudi Arabia. Method In one hospital, a cross-sectional survey was conducted using a convenience sampling technique using a validated questionnaire instrument called the Evidence-Based Practice EBP Questionnaire. The questionnaire was distributed through an online method to 173 participants. Descriptive and inferential statistics Tests were utilized to analyse the retrieved data using the SPSS program. Results One hundred and forty questionnaires were completed and returned, yielding a response rate of 80.9%. Overall, anesthesia teams showed a high positive attitude toward EBP but low levels of knowledge and use of EBP. Participants with higher levels of education and/or work experience exhibited significantly higher levels of knowledge and use of EBP than those who had lower education levels and/or work experience. Also, higher levels of education and/or work experience exhibited a significant positive association toward a higher level of knowledge and use of EBP. However, attitude levels toward EBP did not exhibit either significant or associated. Physicians showed significantly higher knowledge and use of EBP than non-physicians. Lack of knowledge and lack of time due to workload were the leading barriers encountered by anesthesia teams ATs. Conclusion Education level, work experience and job position affect the knowledge, attitude, and use of EBP. Continuous education and minimizing barriers are recommended to enhance the knowledge, attitude, and use of EBP among anesthesia teams in Saudi Arabia.